2022
DOI: 10.1162/neco_a_01506
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Connections in the Primate Ventral Visual Stream Mediate a Trade-Off Between Task Performance and Network Size During Core Object Recognition

Abstract: The computational role of the abundant feedback connections in the ventral visual stream is unclear, enabling humans and nonhuman primates to effortlessly recognize objects across a multitude of viewing conditions. Prior studies have augmented feedforward convolutional neural networks (CNNs) with recurrent connections to study their role in visual processing; however, often these recurrent networks are optimized directly on neural data or the comparative metrics used are undefined for standard feedforward netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…The aligned, simultaneous representational changes in OTC and lower areas imply recurrence between them 36,37 and/or a common top-down input 38 . In either case, we’d expect shared trial-by-trial neural variability between areas 39 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aligned, simultaneous representational changes in OTC and lower areas imply recurrence between them 36,37 and/or a common top-down input 38 . In either case, we’d expect shared trial-by-trial neural variability between areas 39 .…”
Section: Resultsmentioning
confidence: 99%
“…In principle, downstream neurons at a later stage of the visual hierarchy may build a coarse presentation at first based on their initial inputs, which may then help upstream neurons at an earlier hierarchical stage with smaller receptive fields disambiguate 50 what they see, and the disambiguated signals may, in turn, contribute to a refined downstream presentation, and so on. A similar mechanism with different sites of downstream and upstream neurons may underlie object recognition, and its further characterization likely requires fine-grained stimulus design combined with novel computational models 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the advent of deep learning may provide an interesting new approach to understanding the logic of neural circuits deeper in the brain, where the guiding principle is that circuits beyond the sensory periphery must self-organize through local learning rules to achieve whatever tasks are behaviorally necessary. Indeed, some authors have suggested that the hierarchy of visual cortical areas should be understood in analogy with the layers of a deep network (Yamins et al, 2014 ; Yamins and DiCarlo, 2016 ; Schrimpf et al, 2020 ; Muratore et al, 2022 ; Nayebi et al, 2022 ). Of course these circuits ultimately operate on inputs drawn from the natural world, and hence should adapt through learning to both scene statistics and the target task.…”
Section: Challenges For the Futurementioning
confidence: 99%
“…First, the brain's connectivity is highly recurrent at multiple spatial scales, making recurrent neural networks (RNNs) [5] the modeling tool of choice in neuroscience [2,4,6]. The training and analysis of RNNs has advanced theory on the neural basis of perception [7][8][9], motor behavior [10][11][12][13], cognition [14][15][16][17][18][19][20][21][22][23][24][25][26][27], memory and navigation [28,29]. Second, physiological properties of neurons places a greater demand on the emergent computational properties of neural populations.…”
Section: Introductionmentioning
confidence: 99%